Gamification: Blood Donor Apps for IOS Devices - Alvedi Chandra Sabani; Ida Bagus Kerthyayana Manuaba; Erwin Adi (Bina Nusantara University, 2016)
Humans need blood to live and there is no substitute for it. Based on the statistics gathered by the Australian Red Cross, 1 in 3 people will need a blood donation once in their lifetime. However, only 1.5% of Indonesian people donate their blood. In order to rectify this unbalanced blood donation supply and demand, an application named Game4Life was developed and tested. This paper aims to implement ‘gamification’ on iOS devices to encourage users to donate their blood and help to end this shortage. This paper focused on developing features that would help blood donors to schedule their donation as well as a reward and achievement system to motivate future donors and keep them engaged. The deliverable prototype of this paper is implementable and expandable in real life with the cooperation of Palang Merah Indonesia (Red Cross Indonesia) and a company sponsor. Based on the User Acceptance Test results and Palang Merah Indonesia's response, Game4Life has successfully satisfied its scope and requirements.